Relationship of Race/Ethnicity With Door‐to‐Balloon Time and Mortality in Patients Undergoing Primary Percutaneous Coronary Intervention for ST‐Elevation Myocardial Infarction: Findings From Get With the Guidelines–Coronary Artery Disease. Issue 12 (24th September 2013) - Cavender, Matthew A.; Rassi, Andrew N.; Fonarow, Gregg C.; Cannon, Christopher P.; Peacock, W. Frank; Laskey, Warren K.; Hernandez, Adrian F.; Peterson, Eric D.; Cox, Margueritte; Grau‐Sepulveda, Marie; Schwamm, Lee H.; Bhatt, Deepak L.
Abstract Background Prior studies have described racial/ethnic disparities in door‐to‐balloon (DTB) time for patients undergoing primary percutaneous coronary intervention (PCI). We sought to compare DTB time between different racial/ethnic groups undergoing primary PCI for ST‐elevation myocardial infarction in Get With the Guidelines (GWTG). Hypothesis There may be differences in D2B time associated with race/ethnicity. Methods We identified 7445 white (n = 6365), African American (n = 568), and Hispanic (n = 512) patients undergoing primary PCI. Results There were no differences in the median DTB time between white (74 minutes; intraquartile range [IQR], 54–99), African American (77 minutes; IQR, 57–100), and Hispanic (75 minutes; IQR, 56–100) (P = 0.13) patients. There were no crude differences in DTB time ≤90 minutes; however, after adjusting for confounders, African American race was associated with lower odds of DTB time ≤90 minutes (odds ratio [OR]: 0.84; 95% confidence interval [CI]: 0.70‐0.99; P = 0.04). This association was seen in African American males (OR: 0.66; 95% CI: 0.55‐0.80) but not African American females (OR: 1.27; 95% CI: 0.96‐1.68). Overall, Hispanic ethnicity was not associated with a difference in DTB time ≤90 minutes (OR: 0.98; 95% CI: 0.77‐1.25; P = 0.88); although Hispanic males did have a slightly longer median DTB time compared with whites. During the study, the proportion of patients with DTB times ≤90 minutes increased for all groups, and mortality was similar between groups (white 3.8%, African American 3.0%, Hispanic 4.1%, P = 0.62). Conclusions In GWTG‐Coronary Artery Disease, small differences in DTB times persist among different races/ethnicities. However, the proportion achieving DTB times ≤90 minutes has increased substantially for all patients over time, and there was no association between race/ethnicity and in‐hospital mortality.